Karakteristik Kimia Dan Organoleptik Asap Cair Tempurung Kelapa Dalam Menurunkan Cemaran Logam Timbal (Pb) Pada Ikan Cakalang (Katsuwonus pelamis) - Djalil, Jhodi Pratama; Salimi, Yuszda K; Iyabu, Hendri; Bialangi, Nurhayati; Mohamad, Erni; Kunusa, Wiwin Rewini (Jambura Fish Processing Journal, 2024)
This research aims to determine the chemical characteristics of coconut shell liquid smoke and analyze the effectiveness of using liquid smoke in reducing Pb metal contamination in skipjack tuna (Katsuwonus Pelamis). Grade 2 liquid smoke from coconut shells is produced by the Pulubala IKM center through the stages of pyrolysis and distillation. This study employs a completely randomized design (CRD) with two replications. To determine the chemical characteristics of the liquid smoke, the analyzed methods include pH measurement, phenol content, total acidity, protein content, organoleptic value, and the chelating power of heavy metal Pb with variations in the concentration of liquid smoke test solutions AC (undiluted liquid smoke), AC2, AC4, AC6, and AC10 (liquid smoke with the addition of distilled water at 2%, 4%, 6%, and 10%). The results show that the best treatment is obtained from coconut shell liquid smoke with AC concentration (undiluted liquid smoke) having the best characteristics, namely a pH value of 4, phenol content of 1.6469%, total acidity of 14.94 mg/mL, protein content of 0.6083%, and a chelating power for heavy metal Pb of 97.32%. The results of the organoleptic test indicate that overall, the highest score was obtained with a neutral value at the concentration of AC2 (liquid smoke with the addition of 2% distilled water).